Enhancing the Mechanical Robustness of Gold Nanowire Array via Sulfide‐Mediated Growth. Issue 7 (30th April 2022) - Su, Dongmeng; Lam, Zhenhui; Zheng, Yonglong; Wang, Yawen; Liu, Bin; Chen, Hongyu
Abstract : Vertical nanowire arrays (NWAs) have attracted great attention for their outstanding electronic and materials transport properties. Despite the recent progresses, peel‐off of the metal NWAs remains a major challenge for their application. Herein, the peel‐off problem is studied and improved synthesis to solve the problem is discussed. Severe electrode degradation is caused by bubble formation, but even simple cyclic voltammetry scans without major redox chemistry could induce degradation. The robustness of the Au NWAs is found to depend mainly on their surface hydrophilicity. Most importantly, sulfide treatment of the NH2 ‐functionalized substrate is found to give sparser and longer Au NWAs, with greatly improved robustness. Coupled with Pd coating with concomitant hydrophilic treatment, the sulfide‐mediated Au@Pd NWAs could withstand 1 h of constant voltage electrolysis without much loss of the current intensity. Abstract : The peel‐off of nanowire arrays (NWAs) is investigated by monitoring the cyclic voltammetry (CV) current and the electrode appearance. The sparser and longer NWAs obtained by the sulfide‐mediated growth and the following hydrophilic treatment are found to enhance their robustness against peeling off. The understanding and synthetic advance would expand the application of metal NWAs.